2014
DOI: 10.1371/journal.pone.0084734
|View full text |Cite
|
Sign up to set email alerts
|

The Alternative Role of Enterobactin as an Oxidative Stress Protector Allows Escherichia coli Colony Development

Abstract: Numerous bacteria have evolved different iron uptake systems with the ability to make use of their own and heterologous siderophores. However, there is growing evidence attributing alternative roles for siderophores that might explain the potential adaptive advantages of microorganisms having multiple siderophore systems. In this work, we show the requirement of the siderophore enterobactin for Escherichia coli colony development in minimal media. We observed that a strain impaired in enterobactin production (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
64
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(74 citation statements)
references
References 48 publications
(47 reference statements)
7
64
0
1
Order By: Relevance
“…Accordingly, it was presumed that Ent may exert a plethora of key physiological functions that could account for its high metabolic cost (38), aside from acquiring iron to support bacterial growth. Such notion has been demonstrated in studies whereby Ent was shown to be fundamental for E. coli to establish colonization in the mammalian gut (39), develop mature biofilms (40, 41), alleviate oxidative stress (42, 43), and neutralize the anti-microbial activity of MPO (21). The multifaceted property of Ent is further exemplified by our findings that it could inhibit an array of neutrophil functions, including ROS generation, NETs formation, degranulation, phagocytosis and bacterial killing activity.…”
Section: Discussionmentioning
confidence: 95%
“…Accordingly, it was presumed that Ent may exert a plethora of key physiological functions that could account for its high metabolic cost (38), aside from acquiring iron to support bacterial growth. Such notion has been demonstrated in studies whereby Ent was shown to be fundamental for E. coli to establish colonization in the mammalian gut (39), develop mature biofilms (40, 41), alleviate oxidative stress (42, 43), and neutralize the anti-microbial activity of MPO (21). The multifaceted property of Ent is further exemplified by our findings that it could inhibit an array of neutrophil functions, including ROS generation, NETs formation, degranulation, phagocytosis and bacterial killing activity.…”
Section: Discussionmentioning
confidence: 95%
“…4). Siderophores similar to fluvibactin can inhibit bacterial and fungal growth (20,56), and catechol iron chelators have also been suggested to protect bacteria from oxidative stress (57,58). Hence, beside the competitive advantage during surface colonization due to the antibacterial activity of fluvibactin, producers of this compound might as well be protected from oxidative stress, which is a prevalent phenomenon in the marine environment (59).…”
Section: Discussionmentioning
confidence: 99%
“…Notably, this function is associated with the redox activity of the enterobactin catecholates rather than iron transport. 204 Moreover, E. coli strains that cannot produce enterobactin are unable to form colonies on minimal medium. This effect could not be reversed with iron supplementation; however, addition of enterobactin or a reducing agent such as ascorbic acid to the agar allowed the colonies to form, as did anaerobic incubation.…”
Section: Protection From Oxidative Stressmentioning
confidence: 99%
“…On the basis of these results, the catecholate moieties of the siderophore are proposed to scavenge radicals. 204 …”
Section: Protection From Oxidative Stressmentioning
confidence: 99%